Preparing for weight loss surgery : therapist guide - Apple, Robin F. (Robin Faye) (Treatments that work., 2006)
1. Introductory Information for Therapists. 2. Understanding Your Patients Eating Behavior. 3. Helping Your Patient Keep Track of Their Eating. 4. Educating Your Patient about Weighing Behaviors. 5. Pleasurable Alternative Activities. 6. Challenging Eating Situations: People, Places and Foods. 7. Teaching Your Patient about Problem Solving and Cognitive Restructuring. 8. Working with Your Patient on Body Image Issues. 9. Congratulations! Your Patient is on the way to the O.R. 10. What Happens After Surgery?